Pengaruh Persepsi Kualitas, Persepsi Nilai, Persepsi Kepuasan dan Persepsi Diferensiasi terhadap Kesetiaan Merek yang Dimediasi oleh Kepercayaan Merek pada Merek Polki - Pramana, Vina; Wardhana, Ali (Business Management Journal, 2024)
AbstractThe development of household cleaning products continues to expand from year to year creating a potential for companies to increase the number of consumers through quality perception, value perceptions, satisfaction perceptions and differentiation perceptions. The study aims to examine the influence of quality perceptions, value perceptions and satisfaction perceptions on brand loyalty mediated by brand trust in the POLKI brand. The sample in this study had 181 respondents who met the criteria. In this study, data is being processed using Smart PLS 3.0. The results of this study show that brand trust has a significant influence on brand loyalty. There is a significant impact between quality perception, value perception and satisfaction perception on brand trust. There are insignificant influences between the perception of quality, appreciation of value, satisfaction and differentiation perceptions of brand loyality. And there is a minor influence between differential perceptions and brand confidence. In addition, there are significant influences among quality perceptions, appreciations of value and satisfactions perceptions on brand faith mediated by brand trusts.